1998
DOI: 10.7863/jum.1998.17.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Significance of an echogenic intracardiac focus in fetuses at high and low risk for aneuploidy.

Abstract: Our objective was to evaluate the significance of an echogenic intracardiac focus in a mixed population of fetuses at high and low risk for aneuploidy. Over a 1 year period, we prospectively identified all fetuses with an echogenic intracardiac focus seen during prenatal sonography. A detailed structural evaluation was performed on each fetus as permitted by gestational age. The location and number of foci were tabulated prospectively, as were associated abnormalities. Follow-up was obtained by review of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 11 publications
5
80
2
Order By: Relevance
“…[122][123][124][125] Bettelheim et al 122 found EIF located in the left ventricle in 96% of cases, in combined left and right ventricles in 4.3%, and isolated to the right ventricle in just 0.7% (1 of 150). Bromley et al 116 concluded that right-sided and bilateral EIF combined together had an approximately 2-fold greater risk of aneuploidy compared with leftsided foci, and others have also found that echogenic foci involving both ventricles are more associated with aneuploidy. Wax and Philput 123 reported that aneuploidy was more common when echogenic foci involved both ventricles compared with either ventricle alone.…”
Section: Echogenic Intracardiac Foci (Or Papillary Muscle Calcification)mentioning
confidence: 99%
“…[122][123][124][125] Bettelheim et al 122 found EIF located in the left ventricle in 96% of cases, in combined left and right ventricles in 4.3%, and isolated to the right ventricle in just 0.7% (1 of 150). Bromley et al 116 concluded that right-sided and bilateral EIF combined together had an approximately 2-fold greater risk of aneuploidy compared with leftsided foci, and others have also found that echogenic foci involving both ventricles are more associated with aneuploidy. Wax and Philput 123 reported that aneuploidy was more common when echogenic foci involved both ventricles compared with either ventricle alone.…”
Section: Echogenic Intracardiac Foci (Or Papillary Muscle Calcification)mentioning
confidence: 99%
“…In a study of 9263 low-risk pregnancies, 153 fetuses had EIF and none of them had trisomy 21. 19 Bromley et al 20 have shown that the risk of aneuploidy is also increased when EIF is found in fetuses of low-risk pregnant women. Nevertheless, on the basis of current literature there is a strong evidence to support the fact that EIF is more prevalent in fetuses with chromosomal defects specifically trisomy 13 and trisomy 21.…”
Section: 12mentioning
confidence: 99%
“…It is observed in 3-4% of normal fetuses and disappears spontaneously in the third trimester. 39 If the size of echogenic intracardiac focus is large or there are multiple of them, the risk of aneuploidy increases. Bromley et al 40 reported that the risk of aneuploidy is 2 times higher when echogenic intracardiac focuses are in the right ventricle or bilateral than when they are only in the left ventricle.…”
Section: Echogenic Intracardiac Focusmentioning
confidence: 99%